2007
DOI: 10.1111/j.1745-4549.2007.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clove and Tea Tree Oils on Escherichia Coli O157:h7 in Blanched Spinach and Minced Cooked Beef

Abstract: The effectiveness of essential oil application in foods is the result of factor associations such as composition and storage temperatures. The aim was to evaluate the effectiveness of clove and tea tree essential oils to control Escherichia coli O157:H7 on blanched spinach and minced cooked beef exposed at 8 and 20C For both essential oils, the highest concentrations (three and four times minimal inhibitory concentrations) were needed to restrict O157:H7 populations in blanched spinach and minced cooked beef, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 23 publications
2
40
0
1
Order By: Relevance
“…The EOs would be dissolved in the lipid phase of the food and would be less available to act on bacteria that are present in the aqueous phase (22).…”
Section: Antimicrobial Activity Against Vancomycin-resistant Enterocomentioning
confidence: 99%
See 3 more Smart Citations
“…The EOs would be dissolved in the lipid phase of the food and would be less available to act on bacteria that are present in the aqueous phase (22).…”
Section: Antimicrobial Activity Against Vancomycin-resistant Enterocomentioning
confidence: 99%
“…Moreira et al (22) reported that in vitro assays, the maximum E. coli O157:H7 reductions (3. coli O157:H7, depending on the concentration used and the initial bacterial load. These conservative effects were enhanced when we combined the use of the EO with refrigerated storage.…”
Section: Antimicrobial Activity Against Vancomycin-resistant Enterocomentioning
confidence: 99%
See 2 more Smart Citations
“…We can infer that to obtain a positive response, a longer contact time between the film and the system may be necessary (35). The pH of a product can also have an influence on the activities of active agents because the pH can modify the extent of ionization (dissociation/ionization) of certain compounds and consequently affect their activity (28).…”
mentioning
confidence: 99%